New Pharmacological Strategies for the Treatment of Non-Infectious Uveitis. A Minireview - Valenzuela, Rodrigo A.; Flores, Iván; Urrutia, Beatriz; Fuentes, Francisca; Sabat, Pablo E.; Llanos, Carolina; Cuitino, Loreto; Urzua, Cristhian A. (Frontiers in Pharmacology, 2020)
Non-Infectious uveitis is a group of disorders characterized by intraocular inflammation at different levels of the eye and are a leading cause of irreversible blindness in working-age population in the developed world. The goal of uveitis treatment is to control inflammation, prevent recurrences and preserve vision, as well as minimizing the adverse effects of medication. Currently, the standard of care for non-infectious uveitis includes the administration of corticosteroids (CS) as first line agents, but in some patients a more aggressive therapy is required. This includes synthetic immunosuppressants such as metothrexate, mycophenolate mofetil and azathioprine, calcineurinic inhibitors (cyclosporine, tacrolimus) and alkylating agents (cyclophosphamide, chlorambucil). Nevertheless, some patients become intolerant or refractory to CS and conventional immunosuppressive treatment. In these patients, biologic therapy has arisen as an effective therapy. Among the most evaluated treatments, TNF-α inhibitors, IL blockers and anti-CD20 therapy have emerged. In this regard, anti-TNF agents (infliximab and adalimumab), have shown the strongest results in terms of favorable outcomes. In this review, we will discuss recent evidence concerning to the effectiveness of biologic therapy, and present new therapeutic approaches directed against immune components as potential novel therapies for non-infectious uveitis.